Systemic Classification of Wound Dressings: a Review - Martínez-Correa, E.; Osorio-Delgado, M. A.; Henao-Tamayo, L. J.; Castro-Herazo, C. I. (Revista Mexicana de Ingenieria Biomedica, 2020)
Nowadays, there is wide variety of dressings because availability of biomaterials and bioactive components, thus a consensus is needed on their classification, to avoid in understanding their usefulness and their proper handling in clinical practice. Therefore, in this paper a bibliographic review is made using the SCOPUS, ScienceDirect and Web of science databases, with search equations which include the keywords of different types of wound dressings. With this information, we found that dressings can be classified according to their complexity, the nature of the polymeric material, its permeability, its biological interaction with the wound and its therapeutic action, in order to have a detailed definition with all the relevant characteristics to make a proper choice of a dressing. Additionally, a review about the healing process and the types of wounds is included, since this have an important influence on the therapeutic purposes and the correct selection of dressings.